The affective component of racial stereotypes and its relation to attitudes of social distance - Yenko, Rose Marie J. (Philippine Journal of Psychology, 1970)
The questions raised in this paper were generated by the results of Gardner, Wonnacott and Taylor's study in 1968: (1)Can affectless stereotypes of Americans, Chinese, Japanese, and Spanish mestizos be obtained? (2)What is the relationship between the attitudes of social distance towards Americans, Chinese, Japanese, and Spanish mestizos and the presence of absence of affect in the stereotypes of these groups?. Forty-nine college freshmen of the Ateneo de Manila University were the subject population of this study. An adjective check list which was composed of unobtrusive semantic differentials was used to measure stereotypes. The semantic differentials were sets of traits that described the same behavior, but connoted opposing social desirability valences. Two social distance scales - a modified Bogardus scale, and a paired comparisons scale - were used to measure the subjects' attitudes of social distance towards the four groups. A few affectless stereotypes of Americans and Chinese were obtained. The presence of the affectless stereotypes did not negate the affective component found in the American and Chinese stereotypes. A positive affective component was also found in the stereotypes of the Japanese, however, no affectless stereotypes were obtained for the Japanese and the Spanish mestizos. Upon viewing the relationship between the presence of the affective component of the American, Chinese, and Japanese stereotypes and the attitudes of social distance towards these groups, a non-congruent relationship was obtained. Despite the definite direction of the ACS, the direction of the ASD was indeterminate. It was hypothesized that the observed relationship between the ACS and the ASD was affected by contact of the subjects with the members of these racial groups and by the lack of control of image factors that may have been associated with the racial groups concerned.